Szare bloki z wielkiej płyty przytłaczają? Blokowiska w pozanaukowym dyskursie publicznym - Tomczyk, Edyta (Człowiek i Społeczeństwo, 2019)
The article presents the results of a study on the latest non-scientific public discourse on Warsaw large housing estates, with particular emphasis on architectural and urban issues, based on the analysis of press articles from a popular daily regional paper, „Gazeta Stołeczna”, blogs devoted to the city and hip-hop pieces written by Warsaw rappers. Discourse analysis included the identification of the discourse participants, i.e. who is talking to whom?; discourse content analysis, i.e. what is said?; and, finally, determination of the type of discourse and the role of language i.e. how it is said? The article consists of two parts. In the first methodological section a general view over discourse analysis as a tool for conducting interdisciplinary research and a short review of Polish works on discourse in the context of urban research are discussed. The second part of the paper is devoted to the results and conclusions of the study.